الضغوط المهنية و علاقتها بالولاء التنظيمي لدى ممرضي مستشفى هواري بوميدين قصر الحيران الأغواط - بن محجوب حدة; ابتسام بيقع; سمية جقيدل (My University, 2023)
The current study aimed to uncover the relationship between occupational stress and organizational loyalty among nurses working at the Houari Boumediene Hospital in Qasr El Hiran. The sample was tested intentionally consisting of 30 nurses 'and the study relied on the descriptive approach as a research method' and on the questionnaire of professional stress and the questionnaire of organizational loyalty and the study reached the following results: -There is a statistically significant relationship between occupational stress and organizational loyalty among nurses and that this relationship is a direct linear relationship.  There were no statistically significant differences in the occupational pressures of the nurses working in the hospital institution Boumediene in Qasr Al-Hiran due to the variable (age and experience .  There are statistically significant differences in the occupational pressures of nurses working in the hospital institution Houari Boumediene Palace Hiran attributed to the variable (scientific qualification .  There are no statistically significant differences in the organizational loyalty of the nurses working in the hospital institution Houari Boumediene in Qasr Al-Hiran due to the variable (age 'experience' scientific qualification . Keywords: professional pressure - organizational loyalty - nurses.